2014
DOI: 10.4067/s0718-22442014000100010
|View full text |Cite
|
Sign up to set email alerts
|

Análisis Comparativo de los Patrones de Modificaciones Óseas de Dos Carnívoros Sudamericanos: El Gato Montés (Leopardus Geoffroyi) y el Zorro Pampeano (Lycalopex Gymnocercus). Aportes para la Identificación de la Acción de Pequeños Carnívoros en el Registro Arqueológico

Abstract: RESUMENEl objetivo de este trabajo es caracterizar y comparar los patrones de modificaciones óseas producidos por dos carnívoros autóctonos de Sudamérica, el zorro pampeano y el gato montés, sobre partes esqueletarias de pequeños vertebrados. Para esto se realizó una experiencia en un parque zoológico local, ofreciendo 10 conejos en forma controlada, a cada uno de los predadores mencionados. En esta oportunidad se presentan los resultados de los restos no ingeridos, para los cuales se analizó la representación… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 47 publications
1
6
0
10
Order By: Relevance
“…The marks were categorized using the types defined by Binford (1981): pits, punctures, crenulated edges, scores, and furrowing. Finally, using ternary graphs (PAST; Hammer et al 2001), the results were compared with the modifications observed in our experimental studies using rabbit as prey for Pampas fox and Geoffroy's cat (Álvarez et al 2012;Rafuse et al 2014;Massigoge et al 2014). Because only three variables are required in this kind of analyses, the most frequent ones (pits, scores and punctures) were selected for comparison purposes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The marks were categorized using the types defined by Binford (1981): pits, punctures, crenulated edges, scores, and furrowing. Finally, using ternary graphs (PAST; Hammer et al 2001), the results were compared with the modifications observed in our experimental studies using rabbit as prey for Pampas fox and Geoffroy's cat (Álvarez et al 2012;Rafuse et al 2014;Massigoge et al 2014). Because only three variables are required in this kind of analyses, the most frequent ones (pits, scores and punctures) were selected for comparison purposes.…”
Section: Methodsmentioning
confidence: 99%
“…12,200 years BP (Politis 2008). Most archaeological bone assemblages from this region have records of carnivore modifications (Gutiérrez 2006;González 2007;Massigoge 2007Massigoge , 2011Bayón et al 2010;Bonomo and León 2010;Álvarez 2012;Frontini 2012;Stoessel 2012;Álvarez et al 2013;Messineo et al 2013Messineo et al , 2014Rafuse 2013;Alcaraz 2015; among others). Big-sized carnivores inhabited the region until the final Pleistocene (Smilodon populator and Panthera onca; Prevosti and Vizcaino 2006), while only one mid-sized species (puma, Puma concolor) and some small-sized carnivores, including foxes, wildcats, skunks and weasels have inhabited this area since the Early Holocene (Cabrera and Willink 1980).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En el caso del zorro, la muestra recuperada es de 639 especímenes, de los cuales aproximadamente un 86% fueron identificados a nivel anatómico. Si bien en este trabajo no discutiremos la destrucción ósea y la representación de partes esqueletarias resultante, es pertinente mencionar que ambos predadores ocasionan una importante pérdida de huesos, particularmente de costillas y vértebras, impactando significativamente en el Número Mínimo de Individuos inicial de conejos (Rafuse et al 2014). …”
Section: Resultsunclassified
“…Estas categorías de digestión y el patrón de preservación esquelética permiten descartar la acción de depredadores más destructivos de sus presas como carnívoros (Andrews, 1990;Gómez, 2007;Gómez y Kaufmann, 2007;Montalvo et al, 2007;, 2012bÁlvarez et al, 2012;Rafuse et al, 2014) o rapaces diurnas (Andrews, 1990;Gómez, 2007;Montalvo y Tallade, 2009;Montalvo et al, 2014) Gómez (2007). Pseudoscops clamator, Rudzik et al (2015).…”
unclassified